Understanding and Measuring Student Engagement in School: The Results of an International Study From 12 Countries - Lam, Shui-fong (2014)
The objective of the present study was to develop a scale that is appropriate for use internationally to measure affective, behavioral, and cognitive dimensions of student engagement. Psychometric properties of this scale were examined with data of 3,420 students (7th, 8th, and 9th grade) from 12 countries (Austria, Canada, China, Cyprus, Estonia, Greece, Malta, Portugal, Romania, South Korea, the United Kingdom, and the United States). The intraclass correlation of the full-scale scores of student engagement between countries revealed that it was appropriate to aggregate the data from the 12 countries for further analyses. Coefficient alphas revealed good internal consistency. Test–retest reliability coefficients were also acceptable. Confirmatory factor analyses indicated that the data fit well to a second-order model with affective, behavioral, and cognitive engagement as the first-order factors and student engagement as the second-order factor. The results support the use of this scale to measure student engagement as a metaconstruct. Furthermore, the significant correlations of the scale with instructional practices, teacher support, peer support, parent support, emotions, academic performance, and school conduct indicated good concurrent validity of the scale. Considerations and implications regarding the international use of this student engagement in school measure are discussed.